(untitled) (Bangkok, 1994)
This volume represents the proceedings of this international seminar and comprises country position papers from scientists directly involved in monitoring the spread of the disease and also research reports on the latest findings on the role of the different possible infectious agents.
Keywords: Aquatic animals,Fishes,Động vật thủy sản; Health,Diseases,Sức khoẻ